2004
DOI: 10.3989/gya.2004.v55.i2.154
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of cupuassu and cocoa fats

Abstract: RESUMEN Propiedades reológicas de las grasas de cupuaçu y del cacao.La manteca de cacao es un ingrediente muy importante en la formulación de chocolates y es responsable de la mayor parte de sus propiedades (textura, palatibilidad y brillo). En la industria de alimentos, la textura de productos que contienen grasa depende enormemente de las propiedades macroscópicas de la red cristalina de la grasa en el producto final. El cupuaçu es una fruta nativa de la región amazónica y sus semillas pueden ser usadas para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
2
10
0
3
Order By: Relevance
“…It is described in Table 1. This fatty acid profile is in accordance with the findings of previous authors (Saraiva, Cabral, Eberlin, & Catharino, 2009;Silva et al, 2009;Lannes, Medeiros, & Gioielli, 2004), who also concluded that stearic and oleic acids were the most abundant fatty acids in cupuacu butter. Saraiva et al (2009) analyzed cupuacu butter via mass spectrometry and determined that the most abundant triacylglycerols in this fat are SSO (∼ 30 %), OOS+SSL (∼ 20 %), ASO (∼ 13 %) and POS (∼ 10 %) where S = stearic acid, O = oleic acid, A = arachidonic acid and P = palmitic acid).…”
Section: Chemicalssupporting
confidence: 93%
“…It is described in Table 1. This fatty acid profile is in accordance with the findings of previous authors (Saraiva, Cabral, Eberlin, & Catharino, 2009;Silva et al, 2009;Lannes, Medeiros, & Gioielli, 2004), who also concluded that stearic and oleic acids were the most abundant fatty acids in cupuacu butter. Saraiva et al (2009) analyzed cupuacu butter via mass spectrometry and determined that the most abundant triacylglycerols in this fat are SSO (∼ 30 %), OOS+SSL (∼ 20 %), ASO (∼ 13 %) and POS (∼ 10 %) where S = stearic acid, O = oleic acid, A = arachidonic acid and P = palmitic acid).…”
Section: Chemicalssupporting
confidence: 93%
“…Larger films are less stable, because the probability of an unstable spot formation (nucleus of film rupture) increases with the film area, causing thermodynamic instability [34,44]. There is also the possibility that the surface fat crystals may have imbibed into the film between the drops, which would result in a point of weakness in the surface layer and cause coalescence [45,46], and the fact that cupuassu fat shows a lower crystallisation time.…”
Section: Stability Of Emulsionsmentioning
confidence: 99%
“…During processing and/or storage, intraglobular fat (e.g. cream) may solidify to form crystals that can protrude through the interface, leading to droplet coalescence [45,46].…”
Section: Stability Of Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por este motivo o índice de temperagem das formulações F3 e F4, com maior quantidade de manteiga de cupuaçu, atingiram valores fora da referência do fabricante. Porém, ao analisar a curva de temperagem (Figuras 12 e 13) é possível observar-se o padrão esperado para uma curva de temperagem de chocolate corretamente temperado, com um platô intermediário horizontal(LANNES, 2004;SILVA, 2009).Apesar da diferença de valores dos índices de temperagem nenhuma das amostras apresentou mudanças de aparência, durante o estudo de prateleira, como a presença de fat bloom.…”
unclassified